Proximate mechanisms involved in the formation of Secondary Osteon Morphotypes - Skedros, J. G.; Doutré, M. S.; Weaver, D. J. (Osteologie, 2016)
Proximate mechanisms involved in forming extracellular matrix (ECM) variations within and between bones are not yet clear. Deficiencies in the collective understanding of details required to illuminate the process that forms a highly ordered ECM are exposed when considering that there is still significant debate as to the importance of cellular control in the assembly of the ECM vs. the observation of collagen fibrillar “self-assembly” (i. e., occurring devoid of cells). We examined data and opinions with respect to possible mechanisms involved in the formation of distinctly different ECM patterns of secondary osteon morphotypes (SOMs). Important considerations include: (1) stretch within the osteoid during fibrillogenesis, (2) various mechanotransduction mechanisms, and (3) whether or not the formation of regional variations in osteonal ECMs requires osteo blast alignment and/or rotation and migration. We propose that primary cilia of osteoblasts and osteocytes have an important role in their perception of variant-related (vectorial) stimuli, which is deemed essential in the genesis of distinctive and mechanically relevant ECM patterns of SOMs.
Keywords: Osteocyte; osteoblast; osteons; osteon morphotypes; cilia; bone